Monitoring Truck Cranes Operation with the Safety Management System on Construction Sites - Tran, Duc-Hieu; Nguyen, Sy-Nam (International Journal of Sustainable Construction Engineering and Technology, 2024)
In the era of construction digitization, automating construction site management is becoming increasingly feasible by integrating site management systems with on-site facilities and equipment. For mobile cranes, including truck cranes operating at construction sites, safety is a critical concern alongside operational management and productivity. The high susceptibility of truck cranes to unsafe conditions, such as excessive vibrations during operation, underscores the importance of addressing these risks.This article presents a research model focused on managing the vibration and tilt levels of truck cranes as part of the broader occupational safety challenges at construction sites. The study employs the finite element method to develop a structural model and applies analytical techniques to construct a continuous-discrete model of the crane, simulating unsafe conditions during operation.The research further proposes a framework for monitoring crane operations with a safety focus, utilizing sensors and a safety controller device. These components communicate with the on-site safety management system to exchange real-time data, issue safety alerts, and generate warnings. Future studies aim to validate these findings by testing the crane element models and the proposed framework in practical, real-world scenarios.